Analisis Dampak Merger Perbankan Syariah BUMN Pada Laba Bersih Terhadap Kinerja Keuangan - IZZUN KHOIRUN NISSA (ITB AAS INDONESIA Surakarta, 2022)
The development of Islamic banking, which tends to slow down, has prompted the discourse of merging Islamic banks and now in 2021, precisely in February, the beginning of the fact that there was a merger of 3 state-owned Islamic banks, namely: PT Bank Syariah Mandiri, PT BNI Syariah and PT. BRI Syariah. And now it has changed its name to Bank Syariah Indonesia (BSI). One of the reasons for the merger is the desire to have a large, strong and efficient Islamic bank with large assets and financing capabilities, thus making a large contribution to the national economy. So the purpose of this writer is to know the impact of net income before and after the merger on financial performance. In financial performance the variables used are financing, DPK and ROA. Thus resulting in an analysis that apparently financing has a positive impact on net income. so that when the financing increases it will have an effect on increasing the level of net profit. While the effect of ROA on net income results in an analysis that has no effect on net income. So, it can be said that there is an asymmetry between ROA and net profit. Finally, the ROA variable has a positive effect on net income. The positive influence shown by ROA has increased, then profit growth will increase. Keyword : Merger, Financing, DPK, ROA, Net profit